2022
DOI: 10.1186/s12911-022-02081-4
|View full text |Cite
|
Sign up to set email alerts
|

A FHIR has been lit on gICS: facilitating the standardised exchange of informed consent in a large network of university medicine

Abstract: Background The Federal Ministry of Education and Research of Germany (BMBF) funds a network of university medicines (NUM) to support COVID-19 and pandemic research at national level. The “COVID-19 Data Exchange Platform” (CODEX) as part of NUM establishes a harmonised infrastructure that supports research use of COVID-19 datasets. The broad consent (BC) of the Medical Informatics Initiative (MII) is agreed by all German federal states and forms the legal base for data processing. All 34 partici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Our literature review yielded 68 papers, seven of which were relevant. 12 15 22 23 24 25 26 The remaining four papers were retrieved using snowballing. 10 11 14 27 We indicated if an attribute was introduced/used before in the literature for the retrieved papers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our literature review yielded 68 papers, seven of which were relevant. 12 15 22 23 24 25 26 The remaining four papers were retrieved using snowballing. 10 11 14 27 We indicated if an attribute was introduced/used before in the literature for the retrieved papers.…”
Section: Resultsmentioning
confidence: 99%
“…13 Based on stakeholder dialogue, Bialke et al and Lin et al identified ethical, legal, and administrative reasons why patients must give explicit consent to medical treatment. 14,15 Both studies identified major required consent components-such as treatment information, consent, and signature and mapped them into the FHIR Consent Resource to demonstrate its suitability to support the exchange of electronic consent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [2][3][4][5] have demonstrated how various software solutions can be applied to obtain patients' digital and paper-based informed consent when the FHIR standard for managing consent has been insufficient [3,5] or has been limited to the exporting of consent definitions previously defined [4].…”
Section: Objectivesmentioning
confidence: 99%
“…The remaining cluster 4 (in yellow) also (Fast Healthcare Interoperability Resources) context in our selection. This year, a contribution by Bialke et al [13] on the topic of standardized exchange of informed consent in an extensive network of university medicine made it into the best paper selection. The authors discuss the use of FHIR in facilitating the exchange of informed consent and provide insights into the potential implications of using FHIR for informed consent in the field of university medicine.…”
Section: Insights Into the Candidate Papers And Best Papersmentioning
confidence: 99%